2014
DOI: 10.1155/2014/584852
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs 146a and 147b Biomarkers for Colorectal Tumor’s Localization

Abstract: The recently identified class of microRNAs (miRs) provided a new insight into cancer research, since abnormalities of members of microRNAs family have been found in various types of cancer. However, the relationship between five miRNAs (miR146a, miR155, miR21, miR135a, and miR147b) and colorectal cancer remains unclear. In the present study, we examined expression of these miRNAs in 25 pair-matched colon cancer tissues and normal colon mucosa. The expression levels of miR146a, miR155, miR21, miR135a, and miR14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 51 publications
3
20
0
Order By: Relevance
“…The expression of miR-17 and miR-146 was downregulated, while the expression of miR-145 was upregulated. This is consistent with the role of these miRNAs in cancer development—the overexpression of miR-17 and mir-146 is a feature of hyper-proliferating cancer cells [20,59], while the enhanced expression of miR-145 impairs proliferation of the HCT116 colon cancer cell line [60]. …”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The expression of miR-17 and miR-146 was downregulated, while the expression of miR-145 was upregulated. This is consistent with the role of these miRNAs in cancer development—the overexpression of miR-17 and mir-146 is a feature of hyper-proliferating cancer cells [20,59], while the enhanced expression of miR-145 impairs proliferation of the HCT116 colon cancer cell line [60]. …”
Section: Discussionsupporting
confidence: 77%
“…For example, in vitro studies showed that suppression of miR-145 may inhibit proliferation, motility, and invasion of colorectal cancer cell lines (SW620 and LoVo) [18]. The profile of expression miRNAs in colon tissue may also have diagnostic value—the overexpression of miR-17 and downregulation of miR-146 was associated with colon cancer progression [19,20]. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, patients with higher miRNA-31 had higher cancer-specific mortality (HR = 2.06, P = 0.0008), which was consistent with the characteristics of RCC. Omrane et al [47] found that miRNA-146a and miRNA-147b expression was significantly higher in LCC compared to RCC after investigating 25 colon cancer specimens. The result implied that these two miRNAs, especially miRNA-146a, appeared to be markers for LCC.…”
Section: Micrornasmentioning
confidence: 99%
“…MIR146A (upregulated 27.0-fold) (Table 6) is a well-studied microRNA that has been found to decrease LPS-mediated inflammation (71) and attenuate the production of type I interferoninduced antiviral factors (72). Interestingly, this microRNA is found at higher levels in colonic tumors (73), and its potential role in C. concisus infection is evident not only through its upregulation but also through its identification as a key hub transcript which may interact with mRNAs involved in the immune response to C. concisus (Fig. 1C).…”
Section: Figmentioning
confidence: 99%